IMPLEMENTASI MODEL PEMBELAJARAN POE DI SEKOLAH DASAR - Salsabila Salsabila; Nisha Marina; Marhamah Marhamah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
AbstractActiveness during the learning process occurs when the teacher can create a lively learning atmosphere. Students can easily understand the material presented by the teacher by applying a learning model, so that learning outcomes can be achieved based on the learning objectives set. This study aims to improve the thematic learning outcomes of fourth-grade students using the POE model and find out their responses to using the model. The sample of this study amounted to 26 students consisting of 9 boys and 17 girls. The research design uses Kurt Lewin's classroom action research model to plan, implement, observe, and reflect. They were collecting data using observation, tests, and interviews. Data were analyzed descriptively with qualitative and quantitative approaches with the help of STATCAL software. The results showed that the pre-cycle learning completeness score was 7,7%, increased in the first cycle to 46,1%, and increased again to 88,4% in the second cycle. The minimum criteria for student completeness are 75, and the classical percentage is 80. The POE model can make students active in their learning. Students' responses in the interview were happy to learn because the teacher provided motivation and rewards, thus creating enthusiasm always to compete to be the best. Meanwhile, the teacher's response stated that POE could be used as a practical learning model to improve student learning outcomes because the steps stimulate students to think critically in predicting, observing, and explaining from observations.Keywords: Learning Model, POE (predict-observe-explain), Thematic Learning Outcomes.AbstrakKeaktifan pada saat proses pembelajaran terjadi apabila guru mampu membuat suasana pembelajaran hidup dan siswa dapat memahami dengan mudah materi yang disajikan guru dengan menerapkan model pembelajaran, sehingga hasil belajar dapat tercapai berdasarkan tujuan pembelajaran yang telah ditetapkan. Penelitian ini bertujuan untuk meningkatkan hasil belajar tematik siswa kelas IV-C menggunakan model POE dan mengetahui respon mereka dalam penggunaan model tersebut. Sampel penelitian ini berjumlah 26 siswa yang terdiri dari 9 laki-laki dan 17 perempuan. Desain penelitian menggunakan penelitian tindakan kelas model Kurt Lewin yang terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Pengumpulan data menggunakan observasi, tes, dan wawancara. Data dianalisis secara deskriptif dengan pendekatan kualitatif dan kuantitatif dengan bantuan software STATCAL. Hasil penelitian menunjukkan bahwa nilai ketuntasan hasil belajar prasiklus sebesar 7,7%, dan mengalami peningkatan pada siklus I menjadi 46,1% dan meningkat lagi menjadi 88,4% pada siklus II. Kriteria minimal ketuntasan persiswa adalah 75 dan persentase klasikal adalah 80. Model POE dapat membuat siswa aktif dalam belajarnya. Respon siswa pada saat wawancara mereka senang belajar karena diberikan motivasi serta reward, sehingga menimbulkan semangat untuk selalu berlomba-lomba menjadi yang terbaik. Sedangkan respon guru mengatakan bahwa POE bisa dijadikan model pembelajaran yang jitu untuk meningkatkan hasil belajar siswa karena langkah-langkahnya merangsang siswa untuk berpikir kritis dalam memprediksi, mengamati, serta mampu menjelaskan dari hasil pengamatan.Kata Kunci: Model Pembelajaran, POE (predict-observe-explain), Hasil Belajar Tematik